2017
DOI: 10.1186/s12879-017-2476-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of nucleic acid amplification tests (NAATs) in urine for genitourinary tuberculosis: a systematic review and meta-analysis

Abstract: BackgroundGenitourinary tuberculosis is the third most common form of extrapulmonary tuberculosis. Diagnosis is difficult because of unspecific clinical manifestations and low accuracy of conventional tests. Unfortunately, the delayed diagnosis impacts the urinary tract severely. Nucleic acid amplification tests yield fast results, and among these, new technologies can also detect drug resistance. There is lack of consensus regarding the use of these tests in genitourinary tuberculosis; we therefore aimed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
1
21
0
3
Order By: Relevance
“…[16][17] UGTB is a serious, insidious disease, generally developing symptoms only at a late stage. 18 A spontaneous autonephrectomy with a nephrocutaneous fistula due to renal TB was described; the patient had recurrent UTI with ineffective antibacterial therapy but UGTB was not suspected. 19 Also, the case of a recurrent UTI was described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17] UGTB is a serious, insidious disease, generally developing symptoms only at a late stage. 18 A spontaneous autonephrectomy with a nephrocutaneous fistula due to renal TB was described; the patient had recurrent UTI with ineffective antibacterial therapy but UGTB was not suspected. 19 Also, the case of a recurrent UTI was described.…”
Section: Discussionmentioning
confidence: 99%
“…21 Even when suggestive findings such as hematuria, sterile pyuria and recurrent urinary infections are present, we rarely remember this diagnostic possibility. 18 UPEC seems to be a pathogen of major significance to global human health. 22 In Hungary, the five most commonly occurring bacteria were E. coli, Enterococcus faecalis, Klebsiella pneumoniae, Pseudomonas aeruginosa and Proteus mirabilis.…”
Section: Discussionmentioning
confidence: 99%
“…PCR: PCR tests targeting IS6110, hsp65 (Rv0440), mpt64, fbp, mtp40 (Rv2351c), TRC4 (conserved repetitive element) -among others, have been devised using endometrial aspirates, EBs, renal biopsies, menstrual blood and urine specimens [2,4,10] but they often lead to false-positive and false-negative results. Detection of male UGTB within semen samples by PCR has also been reported that revealed superiority over MGIT-960 culture [6].…”
Section: Naatsmentioning
confidence: 99%
“…Urogenital tuberculosis (UGTB) is the second most common form of extrapulmonary TB (EPTB) in developing nations with severe epidemic situations. For example, India (comprising 45% of EPTB cases) and the third most common form in locations with a lower incidence of TB [1,2], which include both renal and genital TB. However, concomitant UGTB and pulmonary TB (PTB) are found in 2-10 and 15-20% of patients in developed and developing nations, respectively [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation